Candida Bloodstream Infections in Italy: Changing Epidemiology during 16 Years of Surveillance. (7th May 2015) - Caggiano, Giuseppina; Coretti, Caterina; Bartolomeo, Nicola; Lovero, Grazia; De Giglio, Osvalda; Montagna, Maria Teresa
Abstract : Although considerable progress has been made in the management of patients with invasive fungal infections, Candida bloodstream infections are still widespread in hospital settings. Incidence rates vary geographically, often because of different patient populations. The aim of the present study was to describe the epidemiology of candidemia, to analyze the trend of species distribution, and to measure the in vitro susceptibility to antifungal drugs in a university Italian hospital from 1998 to 2013. The antifungal susceptibility for all Candida isolates was evaluated by broth microdilution assay (CLSI M27-A3 document). Of 394 episodes of candidemia, the average incidence was 3.06/10 000 admissions. C. albicans and non- albicans Candida species caused 44.2% and 55.8% of the episodes, respectively. C. parapsilosis (62.2%) was the most common non- albicans.    C. albicans predominated in almost all departments whereas C. parapsilosis was found in adult and paediatric oncohaematology units (34.8% and 77.6%, resp.). Overall, mortality occurred in 111 (28.2%) patients. Death occurred most often in intensive care units (47.1%) and specialist surgeries (43.7%). Most of the isolates were susceptible to antifungal drugs, but there was an upward trend for azole (P < 0.05 ). In conclusion, this study emphasizes the importance of monitoring local epidemiologic data and the diversity of patient groups affected.